COMPARATIVE ANALYSIS REGARDING SURFACE-TO-AIR MISSILES GUIDANCE IN TERMS OF USING THE THREE POINTS AND PROPORTIONAL APPROACH METHODS - Cristian George CONSTANTINESCU; Vasile Ioan ŞANDRU; Constantin STRIMBU (Scientific Journal of Silesian University of Technology. Series Transport, 2020)
Surface-Based Air Defence systems are the main actions on the ground means of response in fighting with aerial threats. Effectiveness of response is given by its basic elements as defended area size, type and number of missiles systems or command and control and logistical support. Guiding method means a well-defined law ruling the missile trajectory near the target, depending on target coordinates and motion parameters, to ensure a successful mission. The influence of target routing law on the missile guidance should not be confused with some guidance methods. Therefore, for missile guidance, it is enough to determine (regardless of the guidance method), the target motion equations related only to its coordinate elevation angle, kinematics, azimuth, and weather conditions.